Implying implausibility and undermining versus accepting peoples’ experiences of suicidal ideation and self-harm in Emergency Department psychosocial assessments - Bergen, Clara; Bortolotti, Lisa; Temple, Rachel Kimberley; Fadashe, Catherine; Lee, Carmen; Lim, Michele; McCabe, Rose (Frontiers in Psychiatry, 2023)
Background Patients seeking emergency care for self-harm and suicidality often report they are not believed or taken seriously and there is increasing interest in the concept of epistemic injustice in mental health contexts. Communication practices implying implausibility in a person’s story or undermining their experience have been identified outside healthcare settings e.g., courtrooms where they are used to contest and recharacterize a person’s experience. Aims To investigate communication practices in Emergency Department (ED) psychosocial assessments that may (1) undermine, imply implausibility and recharacterize or (2) accept peoples’ experiences of suicidal ideation and self-harm. Method We micro-analysed practitioner-patient communication in 5 video-recorded psychosocial assessments with people presenting to the ED with self-harm or suicidal ideation, and conducted supplementary analysis of participants’ medical records and post-visit interviews. We describe 3 negative cases where accounts were not accepted and undermined/recharacterized and 2 positive cases where accounts were accepted. Results In the negative cases, practitioners undermined peoples’ experiences of suicidality/self-harm by: not acknowledging or accepting the person’s account; asking questions that implied inconsistency or implausibility; juxtaposing contrasting information to undermine the account; asking questions that asserted a different characterization; and resisting or questioning the person’s account. Multiple practices across the assessment built on each other to assert that the person was not suicidal, did not look or act like they were suicidal; that the person’s decision to attend the ED was not justified; and that self-harming behaviours were not that serious and should be in the person’s control. These alternative characterizations were used to justify decisions not to provide further support or referrals to specialist services. In other cases, communication practices were used to acknowledge, accept and validate suicidality/self-harm and introduce a shared understanding of experiences that patients found helpful. Conclusions These findings advance our understanding of how peoples’ experiences are undermined, a phenomenon which has been reported by patients, leads to further deterioration in their mental health and can discourage future help-seeking even when very unwell. Conversely, acknowledging, accepting and validating suicidality/self-harm and introducing a new way of understanding peoples’ experiences generates shared understanding and may reduce epistemic injustice in mental healthcare interactions.